MANAGEMENT OF EDUCATORS IN PRIVATE TSANAWIYAH MADRASAH ISLAMIC EDUCATIONAL MADRASAH FOUNDATION SEI TUALANG RASO (MTs. S YMPI) TANJUNG BALAI CITY - Rahmat, Rahmat; Hanum OK, Azizah; Nahar, Syamsu (JURNAL TARBIYAH, 2023)
This research is to describe the management of teaching staff at MTs S YMPI ST. Raso Tanjungbalai City. The aim of this research is to reveal how planning, organizing, implementing and supervising teaching staff at MTs YMPI ST. Raso Tanjungbalai City. The method used is qualitative research, with research data collection obtained using triangulation techniques with data collection techniques through documentation, interviews and observation. The steps to analyze data are to collect data, reduce data, present data and then conclude. To test the validity of the data, credibility, transferability, dependability and confirmability tests are used. The results of this research reveal three findings, namely planning of teaching staff at MTs. S YMPI ST. The Tanjungbalai City Raso has been implemented and structured correctly in accordance with existing provisions, namely the organization of teaching staff at MTs. S YMPI ST. Tanjungbalai City Raso has been carried out in accordance with predetermined procedures. As for the implementation of the teaching staff plan at MTs. S YMPI ST. Raso Kota Tanjungbalai is running as desired